Pediatric flecainide pharmacogenomics: a roadmap to delivering precision-based care to pediatrics arrhythmias - Palmen, Ronald; Walton, Mollie; Wagner, Jonathan (Frontiers in Pharmacology, 2024)
Flecainide acetate is class 1c anti-arrhythmic with potent sodium voltage gated channel blockade utilized as second line treatment of tachyarrhythmias in children and adults. Given its narrow therapeutic index, opportunities to individualize drug therapy is of utmost importance for clinicians. Despite efforts to improve anti-arrhythmic drug therapy, knowledges gaps with regards to the impact of variation in the genes relevant to flecainide’s disposition and response remain. This variability is compounded in the developing child where particular drug disposition and response pathways may remain immature. The purpose of this comprehensive review is to outline flecainide’s disposition and response pathways while simultaneously highlighting opportunities for prospective investigation in the pediatric population.